Tinjauan Hukum Ekonomi Islam terhadap Kenaikan Harga Kebutuhan Pokok Menjelang Lebaran Studi Kasus di Pasar Kroya Kabupaten Cilacap - Syafa, Muhammad Aldia (TAWAZUN: Journal of Sharia Economic Law, 2024)
This study examines the Review of Islamic Economic Law on the Increase in Prices of Staples Ahead of Eid, a Case Study on the Kroya Market in Cilacap Regency which consists of three problems, How are the prices of staples ahead of Eid. How is the increase in the price of basic commodities and how is the review of Islamic economic law on the increase in the price of basic commodities ahead of Eid. The type of research used in this study is field research that uses qualitative methods. The research location chosen by the author is located in Kroya Market, Cilacap Regency. The data collection technique uses observation, interview and documentation methods that aim to describe the problem and collect facts as a whole. The results of this study show that the increase in the price of staples ahead of Eid at the Kroya market in Cilacap Regency is based on the prevailing prices in the market and the prices provided by the suppliers of goods and the review of Islamic economic law regarding the increase in the price of staples ahead of Eid in the Kroya market is allowed, because it is in accordance with the concept of price in Islam where the conditions in determining prices are fulfilled in accordance with the principles of price determination and market mechanism in Islam.